Gender comparisons of anthropometric characteristics of young sprint swimmers - Zuniga, J.; Housh, T. J.; Mielke, M.; Hendrix, C. R.; Camic, C. L.; Glen, O.; Housh, D. J.; Schmidt, R. J. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to compare the body composition, body build, and anthropometric characteristics of boy and girl sprint swimmers. Two groups (boys, n = 38 and girls, n = 31) of sprint swimmers (mean age ± SD = 11.03 ± 2.29 and 10.45 ± 2.29 years, respectively) volunteered for this study. The subjects were members of local swimming clubs who competed in sprint swimming events (=200 m). Gender comparisons were made for age, body weight (BW), height (HT), fat-free weight (FFW), percent body fat (%fat), endomorphic rating, mesomorphic rating, ectomorphic rating, sum of 12 diameters, sum of 11 circumferences, biacromial diameter/biiliac diameter, and FFW/HT. The results of the independent t-tests indicated that the only mean differences between the boy and girl sprint swimmers were for % fat (boys = 9.40 ± 5.35% fat; girls = 12.73 ± 6.19% fat) and endomorphic rating (boys = 2.87 ± 0.96; girls = 4.29 ± 1.22). For the current age group of sprint swimmers the only gender differences were for measures associated with body fatness, and there were no differences for body build measures associated with musculoskeletal size, muscularity, skeletal size, total body mass, or body breadth dimensions. These findings suggest that the swimming performance for girls may be improved through training programs designed to reduce body fatness.